The Metaphysics of Being in Aristotle Thales: An Analytical Study - Marwan Ali Hussein (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The problem of existence is one of the most important problems that have plagued philosophers since ancient times. Research and studies have continued on this issue, which philosophers have made one of the main topics of philosophy in addition to the theory of knowledge and values to this day. Heidegger, for example, wonders, in the twentieth century, why was there and was not nothing? This question revealed the crisis of existence among philosophers, until a whole philosophy became stained in the twentieth century in the name of existential philosophy. Hence, this research comes to shed light on this problem through the vision of the first teacher, Aristotle, Thales.The Aristotelian vision was distinguished in the search for existence, as we find a mixture of logical research, cognitive research and natural research that was characterized by the nature of biological studies.The Aristotelian vision was also distinctive because it corrected what had been missed from previous philosophers of Aristotle, especially in the research of causes and their diversity, in addition to the fact that the evidence that Aristotle leads to prove the existence of God, which is the evidence of movement, will appear strongly in Islamic philosophy, especially among the owners of the peripheral philosophy. Likewise among those who hold Christian philosophy, who tried to dye their theological teachings with Aristotelian philosophy.